2008
DOI: 10.1086/587151
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Immigrant Replenishment and the Continuing Significance of Ethnicity and Race

Abstract: The literature on assimilation and ethnic identity formation largely assumes that the durability of ethnic boundaries is a function of the assimilation measures that sociologists commonly employ. But this literature fails to account adequately for the role of immigration patterns in explaining the durability and nature of ethnic boundaries. Using 123 in-depth interviews with later-generation Mexican Americans, this article shows that Mexican immigrant replenishment shapes ethnic boundaries and ethnic identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(120 citation statements)
references
References 39 publications
3
115
1
Order By: Relevance
“…The paper further provides insights into the diversity among the Eritrean diaspora and reveals that the relations between the second-generation Eritreans and the newly arrived generation Eritreans cannot be understood without the political context and the history of Eritrea's diaspora. We have shown that the contemporary arrival of a new generation of Eritrean refugees not only shapes the translocal sphere but also that they present an important new factor in the process of identity formation of those who were born and/or raised in the diaspora (see Jiménez, 2008). We have argued that encounters and interactions with the newly arrived Eritreans both personally and as a group in a discourse thereby represent crucial elements in this process.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The paper further provides insights into the diversity among the Eritrean diaspora and reveals that the relations between the second-generation Eritreans and the newly arrived generation Eritreans cannot be understood without the political context and the history of Eritrea's diaspora. We have shown that the contemporary arrival of a new generation of Eritrean refugees not only shapes the translocal sphere but also that they present an important new factor in the process of identity formation of those who were born and/or raised in the diaspora (see Jiménez, 2008). We have argued that encounters and interactions with the newly arrived Eritreans both personally and as a group in a discourse thereby represent crucial elements in this process.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, identity formation in a translocal context may involve various dynamic spaces of encounters that influence the relation to various locations and the renegotiation of identities. Although new immigrants thereby play an important role, their influence on the identity formation process of post-immigrant generations from the same origin has received only little attention and thus needs to be taken into account in research on identity formation of people with immigrant background (Jiménez, 2008(Jiménez, :1562. The Eritrean diaspora in Switzerland is special due to the two distinct generations of immigration, their tense relationship, and different perception of Eritrean politics that exists among Eritreans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8). The work of Jiménez (2008) also shows that replenishment of the rst generation through continuous immigration from the sending country sharpens intergroup boundaries and re-af rms ethnic identities among Mexican-Americans, thereby slowing down assimilation. The external validity or representativeness of these ndings varies greatly.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%